The Correlation Study Between Debate Mastery and Writing Ability of Jogja Debating Forums’ Members in Year 2012 - Furqanul Hakim (International Conference on Education and Language (ICEL), 2013)
The globalization erais supported by the rapid development of information technology and transportation enable people from different parts of the world living together in one place. In instance, people from Indonesia, may live in other countries for various reasons such as studying, working or traveling. Therefore English language as a tool of communication is needed by them. In teaching language, the best technique should be considered. Debate is one of techniques in teaching language.This study tries to investigate the correlation between debate mastery and writing ability as one of language skills. It uses thirty members of Jogja Debating Forum as samples. The correlation is seen from debate score in their debate exhibition and their writing score from case building note that have been made by themthirty minutes before debate exhibition.The correlation between these two variables can be seen as significant result. There is a signficant correlation between debate mastery and writing ability of Jogja Debating Forum Members in year 2012. The correlation can be proven by the computation data that shows the correlation score. The higher the debate score of a member, the better the writing ability is.